Transition towards a bioeconomy: Comparison of conditions and institutional work in selected industries - Kerstin Wilde; Frans Hermans (Environmental Innovation and Societal Transitions, 2024)
Radical innovations aiming for sustainability usually need to transform existing institutions in order to become successful. From a transition perspective, institutional work is one of the actors' core activities in order to influence the dominant regime. This paper explores how institutional work materialises in an emerging bioeconomy. Our conceptual model shows how an industry's field conditions, combined with the actors' characteristics, shape the pattern of institutional work. We propose a set of categories for the classification of institutional fields and differentiate three forms of institutional work. Empirical evidence on actor characteristics and institutional work originates from the bioeconomy segments of the chemical, plastic and construction materials industries. Our findings lead to a new field typology: the impact on actors' institutional work can be conducive, barricading or exhausting. We recommend to question traditional actor classifications and formulate field specific policy measures for an emerging bioeconomy.
Keywords: 330; bioeconomy; sustainability transition; neoinstitutional theory; institutional work; institutional fields; value chains